The aparent decline of e-mail - Franganillo, Jorge (Anuario ThinkEPI, 2012)
Some companies have begun to restrict the use of e-mail with the conviction that the information overload it causes undermines labor productivity. But the problem is not the tool, but the interruptions caused by excessive exchange of messages, often with irrelevant information. Therefore, the real solution is to establish appropriate management strategies and avoid excessive communication. Some initiatives are committed to moving the internal communication to social media, although it tends to fragment the information required to complete tasks.